2009
DOI: 10.1136/adc.2008.148874
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcal disease in infants: a case control study

Abstract: Independent of birth weight, a number of maternal, birth and neonatal factors are significantly associated with GBS disease. The management of babies with GBS disease results in an appreciable use of hospital resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 23 publications
2
43
0
4
Order By: Relevance
“…In a case control study that included 138 cases and 305 controls,27 it was indicated that the majority of cases (74%) presented in the first week of life, and 89% of them occurred during the first day of life.…”
Section: Discussionmentioning
confidence: 99%
“…In a case control study that included 138 cases and 305 controls,27 it was indicated that the majority of cases (74%) presented in the first week of life, and 89% of them occurred during the first day of life.…”
Section: Discussionmentioning
confidence: 99%
“…Intrapartum fever was the commonest risk factor (31%) for EOD and more frequent than in some other studies (19%) . EOD often starts in utero , which means that IAP is a really pre‐emptive therapy.…”
Section: Discussionmentioning
confidence: 80%
“…[32] But such routine neonatal prophylaxis has not gained wide support and its benefi t remain uncertain. In a UK study of invasive GBS disease, [13,36] 89% of early onset cases were identifi ed on day1. Of those developing clinical features on day 1, 97.6% were noted by 12 hours of age.…”
Section: Management Of Newborn Infantmentioning
confidence: 99%